Differences and Similarities among Parotoid Macrogland Secretions in South American Toads: A Preliminary Biochemical Delineation. (30th April 2013) - Sciani, Juliana Mozer; Angeli, Cláudia Blanes; Antoniazzi, Marta M.; Jared, Carlos; Pimenta, Daniel Carvalho
Abstract : Amphibians are known by cutaneous glands, spread over the skin, containing toxins (proteins, peptides, biogenic amines, steroidal bufadienolides, and alkaloids) used as chemical defense against predators and microbial infection. Toads are characterized by the presence of parotoid macroglands. The common toads have lately been divided into two genera: Bufo (Europe, Asia, and Africa) and Rhinella (South America). Basal Rhaebo genus is exclusively of Central America and Amazon region. Although Rhinella and Rhaebo are related, species may share differences due to the diversity of environments that they live in. In this work, we have performed a biochemical characterization of the components of the poison of eight Rhinella species and one Rhaebo by means of RP-HPLC with either UV or MS detection and by SDS-PAGE, in order to verify whether phylogenetic and biological differences, such as habitat, diet, and defensive strategies, between them may also be reflected in poison composition. Although some components were common among the secretions, we were able to identify exclusive molecules to some species. The fact that closely related animals living in different habitats secrete different molecules into the skin is an indication that biological features, and not only evolution, seem to directly influence the skin secretion composition.